(untitled) (Shahroud Journal of Medical Sciences, 2020)
Background: some studies have shown that there is a correlation between serum uric acid and blood glucose levels so that these changes are not exactly clear. This study was conducted to determine the relationship between uric acid and blood glucose in diabetic patients. Methods: This cross-sectional study was performed on 190 type 2 diabetic (DM) patients in Shahroud by convenience sampling method. FBS, uric acid, triglyceride, and total cholesterol under standard conditions were measured. Patients were divided into four groups in terms of uric acid level. Results: In this study, 53.7% of patients were male. The average age of cases was 58.3 ± 13.5 years. There was a significant difference in uric acid between age groups (Pvalue<0.023), educational levels (Pvalue<0.041), BMI (Pvalue<0.012) and cholesterol (Pvalue<0.002) groups. Also, there was a significant reverse relationship between mean FBS (Pvalue<0.001), blood glucose two hours after feeding (Pvalue<0.001), and HbA1c (Pvalue<0.02) with different levels of uric acid. Conclusions: The results showed that there was a significant and reversal relationship between the levels of uric acid and glucose levels. In order to control the level of uric acid, the level of glucose in these patients is also to be measured and controlled. Keywords: Diabetes mellitus, Blood glucose, Uric acid.